Fatigue characteristic and Weibull analysis of sustainable rubberwood flour/recycled polypropylene composites - Mustafa, Zaleha; Tuan Nawi, Tuan Muhammad Idzuddin; Shamsudin, Zurina; Sheikh Md Fadzullah, Siti Hajar; Dhar Malingam, Sivakumar; Ratanawilai, Thanate (Penerbit Universiti Malaysia Pahang, 2021)
Although there is a perpetual interest in natural fibre composite, the fatigue data and their durability behaviour is still lacking, thus limiting their potential use in high-end applications. In this study, wood polymer composite made from rubberwood flour and recycled polypropylene was subjected to a tension-tension fatigue test in order to investigate their fatigue characteristic. Hysteresis loop was captured in order to establish their stress to number of failure (S-N) curve. The fatigue strength of the composite strongly depends on the stress amplitude. At the lowest stress level, the fatigue life of the composite exceeds the 1.5 million cycles limit, suggesting that the endurance limit for composite materials to be 11.06 MPa. The residual modulus and energy dissipated are plotted as a function of number of fatigue cycles. As the cycles progress, the residual modulus fall and dissipated energy increase indicated the cyclic damage in the composite structure. Two parameters Weibull probability were used to statically analyse the fatigue life and reliability of the rubberwood/recycled polypropylene composite. The S-N curve was plotted at different reliability index (RI = 0.1, 0.368, 0.5, 0.9, 0.99) using Weibull data. This data is used to identify the first failure time and design limits of the materials.